Risk Factors Associated With Lower Bone Mineral Density in Primary Aldosteronism Patients - Lv, Xiaomei; Hu, Huijun; Shen, Chuyu; Zhang, Xiaoyun; Yan, Li; Zhang, Shaoling; Guo, Ying (Frontiers in Endocrinology, 2022)
Purpose The association between primary aldosteronism (PA) and lower bone mineral density (BMD) has raised a concern, but the contributing factors remain unclear. We aim to explore the risk factors for lower BMD in PA patients. Methods We analyzed and compared the data of 60 PA patients with 60 matched essential hypertension (EH) patients. BMD, bone metabolites, and several oxidative stress and inflammation indicators—including C-reactive protein (CRP), superoxide dismutase (SOD), total bilirubin (TBIL), mean platelet volume (MPV), etc.—were assessed and compared in PA and EH patients. Bivariate correlation analysis and multivariate linear regression analysis were performed to explore the factors associated with BMD in PA patients. Results The BMD measured by quantitative computed tomography in PA patients was lower than that in EH patients (141.9 ± 34.0 vs. 158.9 ± 55.9 g/cm3, p = 0.047), especially in patients less than 50 years old. BMD was independently negatively associated with age (standardized β = -0.581, p < 0.001), serum phosphorus (standardized β = -0.203, p = 0.008), urinary calcium excretion (standardized β = -0.185, p = 0.031), and MPV (standardized β = -0.172, p = 0.043) and positively associated with SOD (standardized β = 0.205, p = 0.011) and TBIL (standardized β = 0.212, p = 0.015). Conclusions The PA patients showed a lower BMD than the EH patients, which was associated with age, serum phosphorus, urinary calcium excretion, MPV, SOD, and TBIL. These variables might be potential markers for the assessment of bone loss and efficacy of treatments in PA patients.